Description of Amorbimorpha Kruse, new genus, from Mexico and the southern United States (Lepidoptera: Tortricidae: Sparganothini) - Kruse, James J. (Zootaxa, 2012)
Amorbimorpha Kruse, new genus, is described and illustrated. The genus ranges from Texas, U.S.A., south through Ve-racruz, Mexico, with greatest species richness documented from the middle to upper elevations of central Mexico. Twospecies are described as new: A. powelliana (type species) and A. mackayiana; the latter is the only species in the genusknown from the U.S.A. Also, two new combinations are proposed: A. schausiana (Walsingham, 1913) and A. spadicea(Walsingham, 1913). Male and female genitalia are illustrated for each species where known; A. spadicea is representedby a unique female. Limited biological and life history data are summarized based mainly on laboratory rearings from eggs deposited by confined females of A. powelliana. At least ten additional species remain to be described.